PERANCANGAN SISTEM KENDALI IRIGASI SALURAN SEKUNDER DAN OTOMATISASI PENGUMPULAN SAMPAH PADA ALIRAN AIR SAWAH MENGGUNAKAN ESP32 - Rizky Pramudya; Dewi Laksmiati (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2023)
Agricultural irrigation plays a crucial role in the field of agriculture, particularly in Indonesia, where irrigation systems are commonly employed to supply water to crops. The quality of cultivated rice heavily relies on effective irrigation practices, ensuring that rice plants receive an adequate water supply for optimal growth. However, challenges arise from the inadequate maintenance and pollution of secondary irrigation channels, leading to floods that disrupt crop growth and reduce yields. To address these issues, the author proposes the development of an automated irrigation control and waste collection system using the Esp32 microcontroller, which will be integrated with an IoT system. The device incorporates ultrasonic sensors and load cells as input sensors. The ultrasonic sensors measure water levels, enabling the Esp32 to control a servo motor responsible for opening the irrigation gate. Concurrently, load cells measure the weight of the waste collection tank. Data from these sensors can be directly accessed via the Blynk platform, serving as a monitoring system for water levels and waste load in the collection tank, while also providing notifications based on predefined conditions.